Sustaining Knowledge Translation Practices: A Critical Interpretive Synthesis - Robert A.J. Borst; Rik Wehrens; Roland Bal (International Journal of Health Policy and Management, 2022)
Background  The health policy and systems research literature increasingly observes that knowledge translation (KT) practices are difficult to sustain. An important issue is that it remains unclear what sustainability of KT practices means and how it can be improved. The aim of this study was thus to identify and explain those processes, activities, and efforts in the literature that facilitate the sustaining of KT practices in health policy-making processes.Methods  We used a critical interpretive synthesis (CIS) to review the health policy and systems research and Science and Technology Studies (STS) literature. The STS literature was included as to enrich the review with constructivist social scientific perspectives on sustainability and KT. The CIS methodology allowed for creating new theory by critically combining both literatures. We searched the literature by using PubMed, Google Scholar, Web of Science, and qualitative sampling. Searches were guided by pre-set eligibility criteria and all entries were iteratively analysed using thematic synthesis.Results  Eighty documents were included. Our synthesis suggests a shift from sustainability as an end-goal towards sustaining as actors’ relatively mundane work aimed at making and keeping KT practices productive. This ‘sustaining work’ is an interplay of three processes: (i) translating, (ii) contexting, and (iii) institutionalising. Translating refers to activities aimed at constructing and extending networks. Contexting emphasises the activities needed to create contexts that support KT practices. Institutionalising addresses how actors create, maintain, and disrupt institutions with the aim of sustaining KT practices.Conclusion  The ‘sustaining work’ perspective of our CIS emphasises KT actors’ ongoing work directed at sustaining KT practices. We suggest that this perspective can guide empirical study of sustaining work and that these empirical insights, combined with this CIS, can inform training programmes for KT actors, and thereby improve the sustainability of KT practices.